Short-Term Intake of Chlorogenic Acids Improves Psychomotor Speed and Motor Speed in Adults: A Randomized Crossover Trial - Chika Suzukamo; Ryuji Ochiai; Yuki Mitsui; Noriko Osaki; Takahiro Ono (Brain Sciences, 2022)
Chlorogenic acid (CGA), a polyphenolic compound found in various plants, has been reported to improve cognitive function. However, it remains unclear how long it takes for CGAs to exert their effects. Here, we evaluated the short-term effects of CGAs on cognitive function. We assessed the effects of 2-week CGA intake on cognitive function. The study was carried out as a randomized, double-blind, placebo-controlled, crossover trial. Twenty-six healthy Japanese participants (50–65 years of age) were randomly assigned to either the active beverage (CGAs: 270 mg) or the placebo beverage group daily for 2 weeks. After a 2-week washout period, the participants consumed the other beverages. We assessed cognitive function at baseline and following the first treatment period using the Japanese version of CNS Vital Signs. CGAs significantly improved the scores for psychomotor speed, motor speed, and right and left finger tapping compared to placebo. In addition, processing speed scores improved significantly from baseline only after CGA intake. In conclusion, CGAs were confirmed to improve cognitive function over a short period of two weeks.